Administratīvo sodu process:problēmas un risinājumi - Dreimanis, Agris (Latvijas Universitāte, 2007)
Diplomdarbā aplūkotas būtiskākās administratīvo sodu procesa problēmas. Aplūkotas problēmas saistībā ar iestādes un tiesas kompetenci, procesuālajiem termiņiem, administratīvā soda izpildi. Piedāvāts mainīt esošo administratīvā soda uzlikšanas noilguma regulējumu. Secināts, ka pret tiesneša lēmumu par administratīvā soda uzlikšanu var vērst tādus pašus pagaidu aizsardzības līdzekļus kā pret administratatīvo aktu. Argumentēts, ka gadījumā, ja pārsūdzēts lēmums par administratīvā aresta piemērošanu, šo sodu nevar izpildīt.

In this paperwork are overlooked the main problems of the procedure of administrative punishment. There are overlooked problems of the competence of public authorities in case of administrative offence. There is also analyzed the significance of observance of different procedural terms in the case of administrative offence. There is offered to change present regulation on limitation of administrative liability. There is analyzed regulation about suspension of execution of administrative punishment. Thereby there is ascertained that against judge’s ruling in case of administrative offence can be directed the same provisionally protective measures, which can be directed against administrative act. There is also built up an argument, that accordingly to present regulation the appeal against administrative arrest suspends its execution.
Procedure of Administrative Punishment:Problems and Solutions
Keywords: Tiesības